Impacts of Future Climate Change on the Southern Canadian Prairies: A Paleoenvironmental Perspective - Lemmen, D.; Vance, R.; Wolfe, S.; Last, W. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary Water and soil are critical to the prosperity of the southern Canadian prairies. Both have been strongly influenced by historic climate variability, and by even more significant climate changes that have occurred during the Holocene.These observations, together with general circulation model projections of increasing aridity in this region, raise concerns about the potential impacts of future climate change. Collaborative, multidisciplinary research conducted over the past five years as part of the Palliser Triangle Global Change Project has focussed on geoscientific aspects of climate change in the driest portion of the Canadian prairie provinces. Re-construction of past climates, based on multiple paleolimnological indicators (plantmacrofossils, diatoms, ostracodes, algalpigments, sedimentology, mineralogy, and stable isotope geochemistry), demonstrates that the historic record of roughly 100 years does not adequately capture the range of climatic variability observed during even the last 2000 years. The re-sponse of hydrologie and geomorphicsystems to past changes in climate docu-ments a surprisingly dynamic landscape.The best analogues for projected future climates feature a regional water table more than 4 m below its present level and enhanced wind erosion. The paleoenvironmental record highlights the susceptibility of water and soil resources to climate-induced impacts that are likely to adversely affect human activities in theregion over the next century.